2019
DOI: 10.1051/0004-6361/201834016
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous nano-dust emission in proto-planetary discs: the aliphatic-aromatic components

Abstract: Context. In the interstellar medium, carbon (nano-)grains are a major component of interstellar dust. This solid phase is more vulnerable to processing and destruction than its silicate counterpart. It exhibits a complex, size-dependent evolution due to interactions within different radiative and dynamical environments. Infrared signatures of these nanocarbon grains are seen in a large number of disks around Herbig HAeBe stars. Aims. We probe the composition and evolution of carbon nano-grains at the surface o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 124 publications
(182 reference statements)
4
54
0
1
Order By: Relevance
“…weaker and/or narrower, see e.g. Boutéraon et al 2019 for more details about the variability of the IR-band widths) from those in the diffuse ISM. We here study dust that evolves from dense cloud dust in response to interaction with UV photons.…”
Section: Discrepancy In Irac 45 and Pacs 70mentioning
confidence: 99%
“…weaker and/or narrower, see e.g. Boutéraon et al 2019 for more details about the variability of the IR-band widths) from those in the diffuse ISM. We here study dust that evolves from dense cloud dust in response to interaction with UV photons.…”
Section: Discrepancy In Irac 45 and Pacs 70mentioning
confidence: 99%
“…Characterising the size and properties of these tiny grains through the disks, from internal to external regions, is thus A&A 649, A84 (2021) of prime importance to understand the structure and evolution of PPDs. Boutéraon et al (2019) recently reported several spatially extended near-IR spectral features that are related to aromatic and aliphatic hydrocarbon material in PPDs around Herbig stars, from 10 to 50-100 au, and even in inner gaps that are devoid of large grains. The correlation between aliphatic and aromatic CH stretching bands suggested common carriers for all features.…”
Section: Introductionmentioning
confidence: 99%
“…This crucial fact has driven a detailed consideration of how and where dust evolves in the diffuse and dense ISM (e.g., Stepnik et al 2003;Zhukovska et al 2008;Pino et al 2008;Bernard et al 2008;Jones et al 2013;Wang et al 2013Wang et al , 2014Wang et al , 2015aKöhler et al 2014Köhler et al , 2015Ysard et al 2016;Jones 2016a;Murga et al 2016) and how it evolves in response to the local physical conditions, e.g., gas temperature and density, interstellar radiation field (ISRF). This is particularly important in photo-dissociation regions (PDRs, e.g., Compiègne et al 2008;Abergel et al 2010;Arab et al 2012;Pilleri et al 2012Pilleri et al , 2015Joblin et al 2018) and proto-planetary discs (e.g., Klarmann et al 2017Klarmann et al , 2018Boutéraon et al 2019).…”
Section: Introductionmentioning
confidence: 99%